Photosynthetic limitations in mediterranean plants: A review - Flexas, J.; Diaz-Espejo, a; Gago, J.; Gallé, a; Galmés, J.; Gulías, J.; Medrano, H.; Díaz-Espejo, A. (Environmental and Experimental Botany, 2013)
The aim of the present work is to review the literature concerning photosynthesis of Mediterranean plants. First, we briefly review the most important environmental constraints to photosynthesis, i.e. chilling winter temperatures and summer drought. Then, the review specifically focus on the photosynthetic capacity and photosynthetic limitations of Mediterranean plants under non-stress conditions, to test the general assumption that that the photosynthetic capacity of Mediterranean plants is lower than that of plants from other biomes. It is shown that Mediterranean plants of different life forms and leaf types present, on average, similar photosynthetic capacity to plants from any other biome. However, the mechanisms potentially limiting maximum photosynthesis differ between Mediterranean and non-Mediterranean species. For instance, Mediterranean plants compensate their lower mesophyll conductance to CO2 (gm) with a larger velocity of carboxylation (Vc,max) to achieve similar photosynthesis rates (AN) to non-Mediterranean plants, both factors being associated to a larger leaf mass area (LMA) in Mediterranean species. In contrast, stomatal conductance (gs) was found to be lower only in Mediterranean sclerophytes. On the other hand, Mediterranean sclerophytes and malacophytes (but not herbs and mesophytes) show higher mean intrinsic water use efficiency (AN / gs) due to a combination of higher gm / gs and AN per unit CO2 concentration in the chloroplasts, i.e. carboxylation efficiency. represent specific adaptations of Mediterranean plants to their environment, leading these plants to achieve high AN despite their large LMA, and Mediterranean ecosystems to be Accepted Manuscript The described variations in the mechanistic components of photosynthesis may among those presenting the largest net primary productivities worldwide
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: biochemical limitation; chilling; Drought; Mediterranean; mesophyll conductance limitation; stomatal limitation

Role of Photoprotective Systems of Holm-Oak (Quercus ilex) in the Adaptation to Winter Conditions - García-Plazaola, Josá I.; Artetxe, Unai; Duñabeitia, Miren K.; Becerril, Josá M. (Journal of Plant Physiology, 1999)
Holm-oak (Quercus ilex L.) is a Mediterranean evergreen sclerophyllous species adapted to a wide range of environmental conditions and consequently its leaves must be able to withstand variable stresses. Changes in pigment and antioxidant composition were assessed in relation to chilling stress, light environment and leaf aging. Photosynthetic capacity during winter was rwo-fold higher than in spring. However, the photochemical efficiency of PSI! was reduced in sun leaves probably because of an increased rate of thermal energy dissipation related to the superior zeaxanthin concentration. Lutein, neoxanthin, ~-carotene and the xanthophyll cycle pool increased during winter especially in sun leaves, while lutein epoxide and a-carotene decreased markedly. The main antioxidant accumulated during winter was ascorbate, while glutathione and a-tocopherol were not seasonally affected. Catalase increased in spring as a consequence of higher photorespiration rates, while GR and MOHAR activities were higher in sun leaves during winter. The high MOHAR activity indicates an important role for this enzyme in the adaptation to environmental factors associated to winter. The present study demonstrates that holm-oak is able to acclimate to a variety of environmental stress factors by inducing dramatic changes in their photosynthetic characteristics, pigment composition and antioxidant defences.
Keywords: antioxidants; chilling; Mediterranean evergreens; Quercus ilex; sun/shade; xanthophylls